(untitled) (Third Sector Social Economic Review, 2018)
In today’s marketplace, product recalls are quite common and can be a major obstacle for companies in terms of brand image and brand trust. When companies are faced with a crisis regarding a product, there are various strategies they can choose with regards to product recalls. Some of these strategies include denial, voluntary recall, involuntary recall and extreme effort strategies. These strategies have an impact not only on brand image but also on consumers purchasing intentions. This particular research is carried out to determine the effect of product recalls on brand image and consumers’ purchase intentions. The study was implemented in the city of Ankara and surveys were conducted on 151 adult consumers. Data revealed that voluntary recall and extreme effort strategies have a positive effect on brand image whereas denial strategy led to a negative effect on brand image. It has also been observed that when product recalls have a positive effect on brand image, this has a similar impact on consumers’ purchase intentions. Findings revealed that the opposite situation holds true as well.